Enhancing Intelligence Capacity For Indonesian Peacekeepers In A Dynamic Peacekeeping Landscape - Herman Subagyo Zaesohar; Rodon Pedrason; Asep Adang Supriyadi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
In the constantly evolving realm of peacekeeping, this research delves into strategies to bolster the intelligence capacity of Indonesian peacekeepers. Recognizing the multifaceted challenges presented by the dynamic peacekeeping landscape, the study employs a qualitative analysis approach to explore methods of enhancing the intelligence capabilities of the Indonesian peacekeeping forces. The findings underscore the importance of not only cultivating foundational knowledge in intelligence but also emphasizing specialized competence in adapting to and leveraging evolving methodologies. The study reveals that a comprehensive approach to intelligence capacity building is essential for Indonesian peacekeepers to swiftly and accurately provide nuanced information in the rapidly changing and complex peacekeeping environment. The research further emphasizes the importance of tailored capacity-building programs in fortifying the intelligence capabilities of Indonesian peacekeepers and ensuring their effectiveness in contemporary peacekeeping operations.